Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Hevea MK II Palembang - Ardiwijaya, Dani; Puspasari, Mardiana; Agusria, Lesi (PT Maju Malaqbi Makkarana, 2025)
This study aims 1) to determine the effect of work motivation and work environment on employee performance of PT. Hevea MK II Palembang, 2) to determine the effect of work motivation on employee performance of PT. Hevea MK II Palembang, 3) to determine the effect of work environment on employee performance of PT. Hevea MK II Palembang. This type of research is associative. With the variables used are employee performance (Y), work motivation (X1), work environment (X2). The number of samples in the study were 73 respondents who were taken by simple random sampling. The data used is primary data with data collection methods using questionnaires and documentation. The analysis technique used is multiple linear analysis, F and t hypothesis tests, the coefficient of determination. The results of this study indicate that work motivation and work environment simultaneously have a significant influence on the performance of employees of PT Hevea MK II Palembang. While in the partial test work motivation has a significant effect on employee performance, the work environment has a significant effect on employee performance.